Influence of coating thickness on residual stress and adhesion-strength of cold-sprayed Inconel 718 coatings - Singh, R.; Schruefer, S.; Wilson, S.; Gibmeier, J.; Vassen, R. (Surface & coatings technology, 2018)
In the cold spray process, deposition of particles takes place through intensive plastic deformation upon impact in a solid state at the temperatures well below their melting point. The high particle impact velocity causes high local stresses which lead to deforming the particles and the substrate plastically in the proximity of the particle–substrate interface. As a result, high residual stresses are introduced in cold spray coatings due to the peening effect of the particles collisions with the substrate. In this study, a powder based on the chemical composition of IN 718 was cold-sprayed on IN 718 substrates by using nitrogen gas for an application as a repair tool for aero engine components. The magnitude of the residual stress and its distribution through the thickness were measured by using the hole-drilling and the bending methods. Residual stress was also estimated by using an approach based on the physical process parameters. Mainly compressive residual stresses were observed in cold-sprayed IN 718 coatings. Accumulation of residual stresses in the coatings is highly affected by peening during deposition and it decreases with increase in thickness. It has been observed that the adhesion-strengths of cold-sprayed IN 718 coatings are highly influenced by coating thickness and residual stress states of the coating/substrate system. In the presence of residual stresses in the coatings, adhesion-strength decreases with increasing coating thickness. The energy-release-rate criterion has been used to predict adhesion-strength with increasing coating thickness. Predicted bond-strength values are close to the measured adhesion-strength values and decrease with increase in coating thickness. •IN 718 is cold-sprayed on IN 718 substrates by using nitrogen gas for repair application•Residual stress distribution through the thickness of coatings are measured by using hole-drilling and bending methods.•Residual stress in the coatings decreases with increase in coating thickness.•Adhesion-strengths of cold-sprayed IN 718 coatings are highly influenced by coating thickness and residual stress states of the coating/substrate system.